Prevention of The Use of VPN with Firewall Method Layer 7 Microtic Protocol for Negative Content Filtering and Implementation in RT/RW Net Network (Klatakan Village) - Misbahuddin Misbahuddin (Procedia of Engineering and Life Science, 2022)
The impact of negative content is still widely published in various media, the influence is in the form of pornographic content. To stay away from such content, it is always necessary to emphasize again the basic principles that must be known for using the internet. One of them is to instill healthy internet usage ethics. Internet control can be carried out in the server mechanism in each regional internet network down to the smallest server unit. The web filtering method using the layer 7 protocol feature is one method to achieve the goal of blocking some negative sites and VPNs. In this research, the implementation of web filtering was carried out on the RT/RW net network in Klatakan Pandaan Village. The network is for the benefit of the client, especially the RT/RW net of Klatakan Pandaan Village.